Real-time Tracking and Tracing bei Überseetransporten: Technische Realisierung und wirtschaftliche Auswirkungen der Implementierung - Bastian Steltemeier; Sascha Bioly (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2014)
– The surveillance of supply chains will become more and more important by the rising complexity of the commodity flow. By the integration of telematics systems in the container traffic a tracking and tracing function can be realized. Safety stock and therefore the capital connection of an enterprise can be reduced by the improved prediction of the exact dates of delivery. The consistent surveillance of the transports can reduce the loss of goods and opens a more adaptable interception management. Based on these possibilities this research paper treats the technical realization of a tracking and tracing of containers on oversea transports, as well as the economic aspects of such a system. Therefor the technical bases of the used ZigBee technology are examined. In addition the existing tracking and tracing systems are analyzed on its qualities and compared with the ZigBee-Solution. After the choice and use of suitable economic analysis methods the possibilities as well as chances and risks of the system are specified finally.
Keywords: 650; IT-gestützte Logistik; Lieferkette; Containerverkehr